Rancang Bangun Sistem Informasi Inventori Barang Berbasis Web Pada Toko Infite Elektronik - Ria Amelia; Ubaidillah Ubaidillah; Hadi Syaputra (JOURNAL SAINS STUDENT RESEARCH, 2026)
Infinite Elektronik Store is a business engaged in the sale of electronic products. The inventory management process is still carried out manually using notebooks and communication through WhatsApp, resulting in several problems such as discrepancies between recorded and actual stock, recording errors, slow data retrieval, and delays in inventory reporting. These problems reduce the effectiveness of inventory management and hinder the owner's decision-making process. This study aims to design and develop a Web-Based Inventory Information System for Infinite Elektronik Store to manage inventory data in an integrated, accurate, and real-time manner. The system was developed using the Waterfall software development method, which consists of requirements analysis, system design, implementation, testing, and maintenance. The application was developed using Laravel 11, PHP, MySQL as the database management system, and Visual Studio Code as the development environment. System design utilized Unified Modeling Language (UML), including Use Case Diagrams, Activity Diagrams, Class Diagrams, and Sequence Diagrams. The result of this research is a web-based inventory information system capable of managing product data, supplier data, incoming goods, outgoing goods, stock monitoring, and inventory reports efficiently and accurately. The developed system is expected to improve the effectiveness and efficiency of inventory management, minimize recording errors, provide real-time stock information, and support the store owner in making accurate and timely decisions.